Empirical Investigation of Financial Ratios and Performance of Consumer Goods Manufacturing Companies in Indonesia - Usu, Idrus; Masiaga, Novaliastuti; Hasan, Wahyudin (Institute for Research and Community Service, 2024)
This study investigates the relationship between financial ratios and the financial performance of consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020 to 2023 period. The research was conducted to provide empirical evidence on how internal financial indicators influence company performance, particularly during the post pandemic recovery period. The main objective of this study is to identify which financial ratios, namely profitability, liquidity, solvency, and activity, have the most significant impact on company performance and to determine the extent of their contribution. The research used a quantitative empirical approach with secondary data obtained from audited annual reports, IDX publications, and financial databases. Data were analyzed using descriptive and inferential statistical techniques, including multiple linear regression, supported by classical assumption tests to ensure the validity of the model. The results show that profitability ratios, specifically Return on Assets (ROA) and Return on Equity (ROE), have the strongest positive influence on firm performance. Solvency ratios have a significant negative effect, while liquidity and activity ratios show moderate to weak relationships. The regression model produced an R squared value of 0.63, indicating that financial ratios collectively explain a large portion of performance variation. These findings emphasize the importance of profitability and prudent debt management in achieving financial stability and sustainable growth.